1982
DOI: 10.7164/antibiotics.35.349
|View full text |Cite
|
Sign up to set email alerts
|

Mutants blocked in streptomycin production in Streptomyces griseus - the role of A-factor.

Abstract: Ninety-five streptomycin-nonproducing mutants derived from Streptomyces griseus FT-1 by UV-irradiation could be classified into major two classes by cosynthesis tests. Class I mutants (42 strains) were mutants blocked in the pathway of streptomycin biosynthesis while class II mutants (49 strains) required a factor for streptomycin biosynthesis which was excreted by the parental or class I mutant strains. The factor could be replaced by synthetic A-factor (2S-isocapryloyl-3S-hydroxymethyl-r-butyrolactone) which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(115 citation statements)
references
References 26 publications
7
106
0
1
Order By: Relevance
“…The BprA reaction required NADPH but not NADH. Although we did not determine the stereochemistry at position 3 of the A factor produced in this way, its biological activity suggested that almost the entire population of the molecules are the R-form; the 3R-form is essential for A factor activity (19). Thus, A factor is synthesized through not only pathway A but also pathway B.…”
Section: The Downstream Steps In a Factor Biosynthesis After The Afsamentioning
confidence: 88%
See 1 more Smart Citation
“…The BprA reaction required NADPH but not NADH. Although we did not determine the stereochemistry at position 3 of the A factor produced in this way, its biological activity suggested that almost the entire population of the molecules are the R-form; the 3R-form is essential for A factor activity (19). Thus, A factor is synthesized through not only pathway A but also pathway B.…”
Section: The Downstream Steps In a Factor Biosynthesis After The Afsamentioning
confidence: 88%
“…6C). The extremely low concentration of A factor is still enough for triggering secondary metabolism and morphological development, because exogenous supplementation of A factor at 1 to a few nM is enough to restore streptomycin production of A factor-deficient mutants (19). How is the A factor biosynthesis in such small quantities controlled during the growth?…”
Section: The Variety Of ␥-Butyrolactone Signal Molecules In Streptomymentioning
confidence: 99%
“…Martin (1977) summarized the possible candidates: ATP (Silaeva et al, 1965), adenylate energy charge (Atkinson, 1969), polyphosphates (Harold, 1966) or highly phosphorylated nucleotides. Ochi (1987) emphasized the importance of the level of GTP and its hyperphosphorylated derivative, ppGpp (Gallant, 1979), in controlling synthesis of A-factor, and thereby streptomycin production (Hara & Beppu, 1982), in Streptomyces griseus. Our own studies throw no light on the nature of a phosphorylated regulatory molecule in S. coelicolor ; however, recent work by Bibb & Strauch (1990) appears to rule out ppGpp as a candidate.…”
Section: Discussionmentioning
confidence: 99%
“…4). In a bioautogram, 2) the Rf values of the active substance produced by each of the transformants were the same as that of chemically synthesized A-factor.1) Usually, A-factor-producing Streptormyces strains obtained from culture collections produce 2 to 5 ng of A-factor per colony, while the above transformants of S. albus IFO 3422, S. albus IFO 3710, S. coelicolor A3(2) IFO 3114, and S. viridochromogenes IFO 12376 produced 150, 120, 90 and 120 ng of A-factor, respectively. Acquisition of A-factor productivity appeared neither to influence the morphological features of the transformants nor to cause production of any antimicrobial substance when Bacillus subtilis ATCC 6633 was used as the indicator strain.…”
Section: Methodsmentioning
confidence: 99%